Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia - Churkin, Sergei V.; Kolesnichenko, Kirill A.; Yakovlev, Roman V. (Zootaxa, 2019)
Plebejus chrisreai sp. n. and P. anikini azhbogdo ssp. n. are described from the Dzhungarian Gobi desert and the Transaltajan Gobi desert respectively. External distinctions as well as distinctions of the male genitalia are given for the new taxa and two related species known from Mongolia: Plebejus anikini Yakovlev, 2012 and P. germani Yakovlev, 2012. Genitalia of all the taxa mentioned are illustrated, the aedeagus and valva bear the most valuable taxonomic characters. Females of the new species have an unusual whitish colour of the upperside not known for the christophi species complex before. The distribution of Mongolian taxa and relatives from East Kazakhstan is discussed.